2009
DOI: 10.1097/mca.0b013e32832c4589
|View full text |Cite
|
Sign up to set email alerts
|

Duration of treadmill exercise testing combined with QRS score predicts adverse cardiac outcome at long-term follow-up

Abstract: This study shows that a new index termed the M score, which incorporates QRS score and exercise duration, predicts mortality and occurrence of myocardial infarction at long-term follow-up of high-risk individuals, independently of TET-induced ST-segment changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, total treadmill exercise time and one minute heart rate recovery are also strong predictors of cardiac related events (Ekelund et al, 1988; Hsich et al, 2009) (Cole et al, 1999; Nishime et al, 2000; Watanabe et al, 2001). In addition, the prognostic accuracy of cardiac-related events increases when these physiological responses are combined in a single fitness score or index (Gulati et al, 2005; Mark et al, 1987; Michaelides et al, 2009; Myers et al, 2008; Shaw et al, 1998). Consequently, the combined use of multiple measures of CRF (VO 2 peak, total time on treadmill, and 1-minute HR recovery) are thought to represent a more comprehensive metric of CRF that reflects functional aerobic capacity and individual differences in physical activity (D'Amore and Mora, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, total treadmill exercise time and one minute heart rate recovery are also strong predictors of cardiac related events (Ekelund et al, 1988; Hsich et al, 2009) (Cole et al, 1999; Nishime et al, 2000; Watanabe et al, 2001). In addition, the prognostic accuracy of cardiac-related events increases when these physiological responses are combined in a single fitness score or index (Gulati et al, 2005; Mark et al, 1987; Michaelides et al, 2009; Myers et al, 2008; Shaw et al, 1998). Consequently, the combined use of multiple measures of CRF (VO 2 peak, total time on treadmill, and 1-minute HR recovery) are thought to represent a more comprehensive metric of CRF that reflects functional aerobic capacity and individual differences in physical activity (D'Amore and Mora, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…M score completes all the aforementioned prognostic modalities, since, according to our results, it is significantly, independently, and inversely associated with the risk of myocardial infarction and/or death. In fact, it has also been established that the lower quartile of the M score values (values b 5.758) are independently associated with adverse prognosis [35] (Table 2).…”
Section: Et As a Prognostic Toolmentioning
confidence: 97%
“…It was shown that "Athens score" has proved to be an important alternative in estimating the heart patients and defining their prognosis [34]. Quite recently, in a continuous effort to improve the clinical value of ET, a novel prognostic index was invented, called "M score" (Michaelides score) [35]. M score is a clear number and is calculated by adding the value of the "Athens QRS score" with total exercise duration during ET (in minutes): M score = Athens QRS Score + exercise time.…”
Section: Et As a Prognostic Toolmentioning
confidence: 99%